SERUM VASCULAR ENDOTHELIAL GROWTH FACTOR AFTER BEVACIZUMAB OR RANIBIZUMAB TREATMENT FOR RETINOPATHY OF PREMATURITY. Issue 4 (April 2017) - Wu, Wei-Chi; Shih, Chia-Pang; Lien, Reyin; Wang, Nan-Kai; Chen, Yen-Po; Chao, An-Ning; Chen, Kuan-Jen; Chen, Tun-Lu; Hwang, Yih-Shiou; Lai, Chi-Chun
Abstract : Purpose: To investigate vascular endothelial growth factor (VEGF) levels in the systemic circulation after intravitreal injections of bevacizumab (IVB) or ranibizumab (IVR) in patients with Type 1 retinopathy of prematurity (ROP). Methods: Patients who had Type 1 ROP and received IVB or IVR were enrolled. Serum samples were collected before and up to 12 weeks after IVB or IVR treatment. The main outcome measurements were serum levels of VEGF up to 12 weeks after anti-VEGF treatment. Results: In total, 10 patients with Type 1 ROP were enrolled in this study. All the eyes had complete resolution of abnormal neovascularization of ROP after IVB or IVR. In the direct comparison of IVB with IVR, serum VEGF was found to be suppressed more in patients with Type 1 ROP who received IVB treatment, compared with those who received IVR treatment ( P = 0.01, P = 0.03, and P = 0.03, respectively, 2, 4, and 8 weeks after intravitreal injection). Conclusion: Serum VEGF levels in patients with Type 1 ROP were suppressed for 2 months after treatment with IVB, and VEGF levels were less affected after IVR treatment. Further studies are warranted to investigate the long-term effects of VEGF changes in ROP patients. Abstract : Serum VEGF was found to be reduced by a greater extent in eyes with Type 1 ROP treated with bevacizumab than in eyes treated with ranibizumab.